Improvements in health-related quality of life with belimumab, a B-lymphocyte stimulator-specific inhibitor, in patients with autoantibody-positive systemic lupus erythematosus from the randomised controlled BLISS trials. Issue 5 (22nd March 2013) - Strand, Vibeke; Levy, Roger A; Cervera, Ricard; Petri, Michelle A; Birch, Helen; Freimuth, William W; Zhong, Z John; Clarke, Ann E; ,
Abstract : Objective: Assess the effects of belimumab treatment plus standard systemic lupus erythematosus (SLE) therapy on health-related quality of life (HRQOL) in patients with active, autoantibody-positive SLE. Methods: Patients received standard therapy plus placebo or belimumab 1 or 10 mg/kg in two multicentre, randomised controlled trials of 52 (BLISS-52; N=865) and 76 (BLISS-76; N=819) weeks' duration. Responders were evaluated by SLE Responder Index at week 52. Patient-reported outcome assessments included SF-36, Functional Assessment of Chronic Illness Therapy (FACIT)-Fatigue, and EQ-5D. Results: Mean SF-36 Physical Component Summary (PCS) scores at week 24 was a major secondary endpoint. Baseline SF-36 scores were 1.5 SDs below age-/sex-matched US norms with similar improvement at week 24 across treatment groups. Mean changes from baseline in PCS scores were significantly (p<0.05) greater with belimumab 1 mg/kg (4.20) and 10 mg/kg (4.18) versus placebo (2.96) in BLISS-52, week 52. In BLISS-76, significantly (p<0.05) greater improvements were seen with belimumab 1 mg/kg in PCS (belimumab 1 mg/kg=4.37, 10 mg/kg=3.41 vs placebo=2.85) and Mental Component Summary (MCS) scores (belimumab 1 mg/kg=3.14, 10 mg/kg=2.70 vs placebo=1.40) at week 52, and in MCS score at week 76 (belimumab 1 mg/kg=3.05, 10 mg/kg=2.28 vs placebo=1.36). In pooled analysis, significantly greater improvements in PCS, SF-36 vitality domain, and FACIT-Fatigue scores at week 52 were evident with both belimumab doses. Conclusions: The clinically meaningful improvements in HRQOL in autoantibody-positive patients with active SLE treated with belimumab and standard therapy are consistent with the reductions in disease activity observed in these trials. ClinicalTrials.gov number: NCT00424476, NCT00410384 .